The Effectiveness of Educational Videos in Improving Knowledge in Preschool Children - Iskandar, Siska; Indaryani, Indaryani (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Early childhood education (PAUD) is a crucial period in a child's cognitive, social, and emotional development. At this age, children begin to develop the foundations of skills that will shape their thinking patterns and behavior in the future. Therefore, it is important for educators to provide learning experiences that are fun, engaging, and developmentally appropriate. One increasingly popular approach to supporting early childhood education is the use of educational videos. The purpose of this study was to determine the effectiveness of educational videos in increasing knowledge in preschool children. This research method was quasi-experimental. Sampling was carried out using an accidental sampling technique. Data were analyzed using the Wilcoxon test. The results showed that educational videos had a significant effect on increasing knowledge in preschool children (p = 0.002). This study recommends that educational videos can be used as a learning medium to help increase knowledge in school-age children